The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1093/ptj/pzab052
|View full text |Cite
|
Sign up to set email alerts
|

Specific Contribution of Quadriceps Muscle Strength, Endurance, and Power to Functional Exercise Capacity in People With Chronic Obstructive Pulmonary Disease: A Multicenter Study

Abstract: Objective Various functional muscle properties affect different aspects of functional exercise capacity in people with COPD. The purpose of this study was to investigate the contribution of quadriceps muscle strength, endurance, and power to the 6-minute walking distance (6MWD) and the 1-minute sit-to-stand test (1STS) performance in people with COPD. Methods The study was a prospective, multicenter cross-sectional study. Ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 43 publications
1
17
1
Order By: Relevance
“…A previous study has shown isometric quadriceps muscle strength to be a predictor of response to PR in the 6MWT [42]. However, we did not find it as a predictor and a recent study found no correlations between isometric measurements of muscle function and the 1 min STS, with muscle power measured by isokinetic or the 5-time STS being the main contributor to the 1 min STS and the 6MWT performance [43]. Hence, dynamic measurements and more robust measures (e.g., isokinetic) should be further explored in the future, as they could be highly relevant to assess and predict the response to PR.…”
Section: Discussioncontrasting
confidence: 99%
“…A previous study has shown isometric quadriceps muscle strength to be a predictor of response to PR in the 6MWT [42]. However, we did not find it as a predictor and a recent study found no correlations between isometric measurements of muscle function and the 1 min STS, with muscle power measured by isokinetic or the 5-time STS being the main contributor to the 1 min STS and the 6MWT performance [43]. Hence, dynamic measurements and more robust measures (e.g., isokinetic) should be further explored in the future, as they could be highly relevant to assess and predict the response to PR.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, taken together, our results support and extend previous observations (Sale, 1988;Folland and Williams, 2007;Škarabot et al, 2021) by suggesting that training volume, and specifically the continued progression of training volume after the initial weeks of training, is necessary to enable morphological and structural adaptations and thus, counteract quadriceps dysfunction within the COPD population. These findings are relevant to COPD management considering the high prevalence and adverse consequences of quadriceps dysfunction in this population (Swallow et al, 2007;Maltais et al, 2014;Frykholm, 2020;Géphine et al, 2021).…”
Section: Discussionmentioning
confidence: 86%
“…Elastic work was measured during the first set from the number of repetitions multiplied by the load provided by the elastic band ([Kg] at 100% elongation)( Nyberg et al, 2021 ). Importantly, isokinetic and elastic assessments were performed using valid and reliable test procedures for COPD ( Evans et al, 2014 ; Nyberg et al, 2018 ; Frykholm et al, 2019 ; Frykholm, 2020 ; Géphine et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to provide individualized exercise prescriptions to patients with COPD, several muscle properties that may contribute to skeletal muscle dysfunction need to be assessed 8 . For example, the modality (i.e., isometric, concentric, and eccentric), velocity (i.e., muscle power and rate of force development (RFD)), and fluctuation (i.e., force steadiness) of muscle contraction produce different effects on skeletal muscle function in older healthy adults 9 .…”
Section: Introductionmentioning
confidence: 99%